Magic and Ritual in Iron Age Veneto, Italy (Papers from the Institute of Archaeology, 2010)
In this article I discuss the possibility that the Iron Age Veneti of Northern Italy believed in magic. By drawing on ethno-historical comparisons and contextual analysis, I suggest that items such as pierced shells, coral, amber, glass beads and bronze pendants were possibly employed as amulets by children, women and, far more rarely, by men. I also examine the placing of selected non-edible animal remains such as horns, teeth, and astragali (knucklebones) in ritual contexts, suggesting than their meaning, whether magical, religious or more mundane, can be understood only through a careful evaluation of the circumstances of deposition. I finally point out that the study of magic in prehistory has been often passed over and devalued, probably for a lack of written sources and proper evidence. On the contrary, I argue that a more holistic approach to ritual and to the several layers of meaning embedded in magical objects can offer valuable insights into wider issues such as the management of power and the construction of past individuals' social and personal identities.